Impact of Goal-Oriented Therapy with Different Infusion Media on Pulmonary Extravascular Water Levels in Cardiac Surgery Patients - G. B. Moroz; E. V. Fominsky; A. N. Shilova; A. M. Karaskov; I. A. Kornilov; M. G. Pustovetova; V. V. Lomivorotov (Общая реаниматология, 2015)
Objective: to study the impact of goal-oriented infusion therapy using balanced salt solution, 4% succinylated gelatin, and 6% hydroxyethyl starch 130/0.42 solution on pulmonary extravascular water levels in coronary heart disease patients operated on under extracorporeal circulation.Materials and methods. A prospective, randomized, single-blind clinical study investigating the impact of goal-oriented infusion therapy using balanced salt solution, 4% succinylated gelatin, and 6% hydroxyethyl starch 130/0.42 solution on pulmonary extravascular water levels was conducted in coronary heart disease patents operated on under extracorporeal circulation. The hemodynamic target was the global end-diastolic volume index which was maintained in the range from 680 to 850 ml/m2. Pulmonary extravascular water was measured by a transpulmonary thermodilution technique; hydrobalance, lactate, mixed venous oxygen saturation, hemodynamic parameters, and troponin I concentrations were also investigated.Results. Analysis of the values of the pulmonary extravascular water index revealed no differences between the groups in pulmonary extravascular water levels throughout the study. Large volumes of balanced crystalloid solution were required to maintain intraoperative and postoperative hemodynamics. Balance after surgery was considerably higher and amounted to 2000 [1415—2200] ml in the crystalloid group, 1020 [650—1563] ml in the gelatin group, and 1070 [550—1675] ml in the hydroxyethyl starch solution (p=0.001). Mixed venous oxygen saturation, lactate, and troponin I concentrations were comparable between the groups at the study stages.Conclusion. It was found the infusion therapy using balanced salt solution failed to result in an increase in pulmonary extravascular water levels in coronary heart disease patients operated on under extracorporeal circulation as did colloid solution-based infusion therapy. Achieving hemodynamic targets requires a large volume of crystalloid solution than the use of colloid infusion solution.